TRANSFORMERS CHANGING THE NUMBER OF PHASES - Karimov , Ne’matulla Ubaydulla o‘g‘li (Educational Research in Universal Sciences, 2023)
Analysis of the effect of moisture on the transformer windings, drying of transformer windings, drying standard, winding methods, requirements for post-drying transformer, purpose of transformer drying, technical means, the main factors affecting the drying effect of the transformer given.